Cystic cerebellar dysplasia and biallelic LAMA1 mutations: a lamininopathy associated with tics, obsessive compulsive traits and myopia due to cell adhesion and migration defects. Issue 5 (13th January 2016) - Vilboux, Thierry; Malicdan, May Christine V; Chang, Yun Min; Guo, Jennifer; Zerfas, Patricia M; Stephen, Joshi; Cullinane, Andrew R; Bryant, Joy; Fischer, Roxanne; Brooks, Brian P; Zein, Wadih M; Wiggs, Edythe A; et al.
Abstract : Background: Laminins are heterotrimeric complexes, consisting of α, β and γ subunits that form a major component of basement membranes and extracellular matrix. Laminin complexes have different, but often overlapping, distributions and functions. Methods: Under our clinical protocol, NCT00068224, we have performed extensive clinical and neuropsychiatric phenotyping, neuroimaging and molecular analysis in patients with laminin α1 ( LAMA1 )-associated lamininopathy. We investigated the consequence of mutations in LAMA1 using patient-derived fibroblasts and neuronal cells derived from neuronal stem cells. Results: In this paper we describe individuals with biallelic mutations in LAMA1, all of whom had the cerebellar dysplasia, myopia and retinal dystrophy, in addition to obsessive compulsive traits, tics and anxiety. Patient-derived fibroblasts have impaired adhesion, reduced migration, abnormal morphology and increased apoptosis due to impaired activation of Cdc42, a member of the Rho family of GTPases that is involved in cytoskeletal dynamics. LAMA1 knockdown in human neuronal cells also showed abnormal morphology and filopodia formation, supporting the importance of LAMA1 in neuronal migration, and marking these cells potentially useful tools for disease modelling and therapeutic target discovery. Conclusion: This paper broadens the phenotypes associated with LAMA1 mutations. We demonstrate that LAMA1 deficiency can lead to alteration in cytoskeletal dynamics, which may invariably lead to alteration in dendrite growth and axonal formation. Estimation of disease prevalence based on population studies in LAMA1 reveals a prevalence of 1–20 in 1 000 000. Trial registration number: NCT00068224